STUDI AWAL POTENSI CANGKANG TELUR SEBAGAI BAHAN BAKU BIO-KALSIUM OKSIDA MELALUI PROSES SINTERING DAN ANALISIS (X-ray Fluorescence) XRF: STUDI KASUS DARI LAMPUNG - Satria N, Vastigo; Ojahan R, Tumpal (Bhinneka Multidisiplin Journal, 2025)
Eggshell is a household waste that is rich in calcium carbonate (CaCO₃) and has potential as a bio-calcium oxide (CaO) raw material. Lampung Province, one of Indonesia's egg production centers, produces a considerable number of eggshells; however, the processing has not been optimal. This study aims to evaluate the utilization of eggshells as raw material for CaO through sintering and characterization using X-ray fluorescence (XRF). The processing included washing, drying, grinding, and roasting at 900°C. XRF analysis showed a CaO content of 98.865%, with minimal impurities. The findings suggest that local eggshells can serve as an alternative raw material for CaO, supporting the circular economy in MSMEs and communities, while also being environmentally friendly for both the agricultural and industrial sectors.